Common SNP-Based Haplotype Analysis of the 4p16.3 Huntington Disease Gene Region - Lee, Jong-Min; Gillis, Tammy; Mysore, Jayalakshmi Srinidhi; Ramos, Eliana Marisa; Myers, Richard H.; Hayden, Michael R.; Morrison, Patrick J.; Nance, Martha; Ross, Christopher A.; Margolis, Russell L.; Squitieri, Ferdinando; Griguoli, Annamaria; et al. (American journal of human genetics, 2012)
Age at the onset of motor symptoms in Huntington disease (HD) is determined largely by the length of a CAG repeat expansion in HTT but is also influenced by other genetic factors. We tested whether common genetic variation near the mutation site is associated with differences in the distribution of expanded CAG alleles or age at the onset of motor symptoms. To define disease-associated single-nucleotide polymorphisms (SNPs), we compared 4p16.3 SNPs in HD subjects with population controls in a case:control strategy, which revealed that the strongest signals occurred at a great distance from the HD mutation as a result of “synthetic association” with SNP alleles that are of low frequency in population controls. Detailed analysis delineated a prominent ancestral haplotype that accounted for ∼50% of HD chromosomes and extended to at least 938 kb on about half of these. Together, the seven most abundant haplotypes accounted for ∼83% of HD chromosomes. Neither the extended shared haplotype nor the individual local HTT haplotypes were associated with altered CAG-repeat length distribution or residual age at the onset of motor symptoms, arguing against modification of these disease features by common cis-regulatory elements. Similarly, the 11 most frequent control haplotypes showed no trans-modifier effect on age at the onset of motor symptoms. Our results argue against common local regulatory variation as a factor influencing HD pathogenesis, suggesting that genetic modifiers be sought elsewhere in the genome. They also indicate that genome-wide association analysis with a small number of cases can be effective for regional localization of genetic defects, even when a founder effect accounts for only a fraction of the disorder.